Pengaruh Cara Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Geografi Di Sma Negeri 2 Pekalongan - Natakusuma, Adhitya; Suroso, Suroso; Hardati, Puji (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2017)
A good study result supported by many factors, such as how students learn. Based on the data values of repeat daily students in geography subject (2016/2017), 181 of 277 students (65,34%) X IPS and 82 of 120 students (68,33%) XI IPS SMA Negeri 2 Pekalongan get value of geography subject has not yet reached the KKM. The purpose of the research to find out how student learning, results of students learning, influence of how to learn against students learning result. Analysis using descriptive frecuency to know how to students learn, results of student learning using descriptive analysis, influence of how to learn using simple linier regression analysis method. The results showed that how student learning generally already regular, the average of students learning result has not yet reached the value of KKM, influence how to student learn showed that the increase of how to learn against the results of the study is 0,51 with the positive regression coefficient. The conclusion of the research there is influence of how to students learn against students learning result in the geography subject. The advices are let students to choose the how to learn proper for themself, the teachers should pay attention to the results of student learning in geography subject. Hasil belajar yang baik didukung oleh banyak faktor, seperti cara belajar siswa. Berdasarkan data nilai ulangan harian siswa mata pelajaran geografi tahun 2016/2017 dapat diketahui bahwa 181 dari 277 (65,34%) siswa kelas X IPS dan 82 dari 120 (68,33%) siswa kelas XI IPS SMA Negeri 2 Pekalongan mendapatkan nilai ulangan geografi yang belum mencapai KKM. Tujuan penelitian untuk mengetahui cara belajar siswa, hasil belajar siswa, pengaruh cara belajar terhadap hasil belajar siswa. Analisis data cara belajar menggunakan deskriptif frekuensi, hasil belajar siswa menggunakan analisis deskriptif, pengaruh cara belajar terhadap hasil belajar siswa menggunakan metode analisis regresi linier sederhana. Hasil penelitian menunjukkan cara belajar siswa secara keseluruhan sudah teratur, rata-rata nilai hasil belajar siswa belum mencapai nilai KKM, pengaruh kenaikan cara belajar terhadap hasil belajar siswa sebesar 0,51 dengan koefisien regresinya positif. Simpulan adalah terdapat pengaruh cara belajar terhadap hasil belajar siswa pada mata pelajaran geografi. Saran adalah siswa hendaknya memilih cara belajar yang tepat, guru hendaknya memperhatikan hasil belajar siswa mata pelajaran geografi.